2021
DOI: 10.1186/s13018-021-02376-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of nomogram to predict distant metastasis in osteosarcoma: a retrospective study

Abstract: Background Osteosarcoma is most common malignant bone tumors. OS patients with metastasis have a poor prognosis. There are few tools to assess metastasis; we want to establish a nomogram to evaluate metastasis of osteosarcoma. Methods Data from the Surveillance, Epidemiology, and End Results (SEER) database of patients with osteosarcoma were retrieved for retrospective analysis. We identify risk factors through univariate logistic regression and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…To date, most studies stopped at independent risk factors and only one realistic model has been established to predict the risk of DM in osteosarcoma patients. In the similar predictive tool established by Li et al (40), surgery, a post-diagnosis treatment was included in the nomogram for the diagnosis of DM. This sequential relationship was reverse and irrational, resulting in the model's uselessness.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies stopped at independent risk factors and only one realistic model has been established to predict the risk of DM in osteosarcoma patients. In the similar predictive tool established by Li et al (40), surgery, a post-diagnosis treatment was included in the nomogram for the diagnosis of DM. This sequential relationship was reverse and irrational, resulting in the model's uselessness.…”
Section: Discussionmentioning
confidence: 99%
“…We used LASSO regression analysis to identify ve risk factors for metastasis of spinal and pelvic osteosarcoma:sex,race,grade,number of primary tumor and surgery.Our study showed that female patients and black patients with spinal and pelvic osteosarcoma were less likely to metastasis,which may provide some reference for clinical treatment decisions.Tumor grade is the description of a tumor based on how abnormal the tumor cells and the tumor tissue look under a microscope [4].In our study,the high grade was a risk factor for metastasis of spinal and pelvic osteosarcoma,which should be related to the rapid growth and diffusion of poorly differentiated or undifferentiated tumor cells.In addition,we found that patients with single primary tumors are more likely to metastasize than patients with multiple primary.There are no studies on relationship between number of primary tumor and distant metastasis of spinal and pelvic osteosarcoma,currently.We thought that molecular and biochemical studies of tumors may be needed to explain this.…”
Section: Discussionmentioning
confidence: 74%
“…Osteosarcoma is the most common primary malignant bone tumor,it was reported that the annual prevalence of osteosarcoma ranges 0.2-3 cases per 100,000 people [1].However,spinal and pelvic osteosarcoma is more rare compared with osteosarcoma in other sites.It was reported that spinal osteosarcoma accounts for 3% of all osteosarcomas, while pelvic osteosarcoma accounts for less than 10% of all osteosarcomas [2,3].There are some studies on prediction of distant metastasis of osteosarcoma in all sites [4,5].Nonetheless,there was no similar studies on prediction of distant metastasis of spinal and pelvic osteosarcoma because of low incidence.…”
Section: Introductionmentioning
confidence: 99%
“…It can help clinicians better diagnose and determine treatment options. Applying nomograms to assess metastatic status is necessary (48). Nomograms are rarely reported in predicting metastasis in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%